Using digital badges design principles in professional continuing education programs: a scoping review - Canales, Ismael (2020)
Digital badges are visual representations of a skill, ability or knowledge acquired by a person. Their practical usefulness is to grant these features visibility through broadcasting on online platforms, in addition to storing and publishing evidence and data about the depicted achievement. This new technology is capable of transforming accreditation and evaluation processes for educational and corporate contexts, by providing specific information participants performance in training or work related activities. An exploratory review of sixteen digital badge projects applied in continuing professional education programs was carried out. Details on the design trends and results of these projects were published in twenty documents registered in Scopus and Web of Science. It was determined that the most used design principles were those related to the recognition and evaluation of competences and skills, a situation that agrees with the interest of the participants in that the knowledge learned obtain greater visibility and usefulness for their professional development. In any case, it is recommended to offer more information about the benefits of digital badges to enrich and promote learning experiences in similar educational programs.